HUBUNGAN RESPON TIME SELAMA PANDEMIC COVID-19 DENGAN KEPUASAN PASIEN DI INSTALASI GAWAT DARURAT RUMAH SAKIT UMUM DAERAH SAPARUA - Silvianovelista R Losoiyo; Erika Natasya Makalipessy (Pasapua Health Journal, 2022)
Introduction: The Emergency Room (IGD) is a service unit in a hospital that provides first aid and is the first entry point for patients with emergency conditions. Emergency management in the Hospital Emergency Room (IGD) has a philosophy that is Time Saving it’s Live Saving which usually means that time is life or all actions taken during an emergency condition must be truly effective and efficient. Emergency departments are managed to handle life- threatening emergency patients involving trained professionals and supported by special equipment, so that nurses can provide patient care quickly and accurately. Accuracy of service in the Emergency Room must be supported by the implementation of the correct triage. Method: the research design to be used is an analytic survey design with or a cross-sectional study approach that aims to analyze the relationship between response time in the Covid-19 pandemic and patient satisfaction. Results: 33 respondents who responded on time (75.0%) said they were satisfied, and 6 people (13.6%) said they were not satisfied. Meanwhile, 4 respondents (9.1%) claimed to be dissatisfied and 1 person (2.3%) claimed to be satisfied. Conclusion: The results of the chi square test show a significant value (p = 0.01 <0.005) so that H0 is rejected, therefore it can be concluded that there is a relationship between response time in the Covid-19 pandemic and patient satisfaction in the emergency department at the RSUD Hospital saparua. Suggestion: Specifically for the Saparua Region, Maluku Province. It is hoped that the nurses and other health teams can improve health services for the community and prioritize speed and accuracy.